Armazenamento refrigerado, em atmosfera modificada e controlada na conservação das qualidades físicoquímicas e sensoriais de cultivares de feijão carioca - Franco, Fernanda Wouters (2015)
The common bean (Phaseolus vulgaris L.) has a high nutritional value due to the content of proteins, carbohydrates, minerals and vitamins and has great importance as an economic food to Brazil. After the harvest, the grain enters a deterioration process, intensified in lighter seed coat grains as cultivars of the Carioca group, used in this study. In a conventional storage in natural environmental conditions, this degradation occurs more rapidly due to factors such as high heat and humidity, but also due to the presence of microorganisms responsible for damage to the beans. Thus, new approaches to storage are required to reduce post-harvest losses. The cold storage, by reducing the temperature enables a greater retention for a longer period. Whereas new methods of conservation such as hermetic systems with modified atmosphere and controlled atmosphere have shown good results in maintaining grain quality, this study aimed to evaluate the effect of cold storage and atmosphere modified and controlled in the conservation of quality cultivars carioca beans. For this, 'Pérola' and 'BRS Estilo' beans were collected in Vacaria city-RS, in March, season of 2014. There were analyzes of crude protein, fat, moisture, ash, tegument color, cooking time, viscosity and sensory analysis intensity ranking test. The concentration of 1% O2 compared to the other treatments resulted in the highest percentage of crude protein in beans 'Pérolal'. In relation to the fat content, higher values were observed in CA at concentrations 2, 4 and 6% O2 for longer periods for the two cultivars. Ash and total carbohydrates showed no significant difference in either storage times for any of the two cultivars. CA O2 at low concentrations (1%, 2%, 4% and 6%) decreased the darkening process, guaranteeing a better maintenance of the original color for both cultivars, in five and eleven months of storage. The refrigerated storage at 10ºC after five months resulted in lower cooking times for the two cultivars, besides maintaining longer the fraction bean lipids 'Pérola' and present less intense sensory analysis for consistency in this cultivar. Regarding flavor and odor in the beans 'Pérola' was most intense in samples subjected to CA 1% O2 and this same treatment was effective with regard to color because it was considered by the judges as the beans with less color depth, meaning be lighter, which is desired for growing the Carioca group. Sensorially, the panel also considered that this low concentration of 1% O2, results in a higher viscosity, i.e. a thicker broth. For 'BRS Estilo' beans, treatment with high concentrations of CO2 (11% O2 + 18% CO2), showed the highest sums to the parameters taste, odor and viscosity of the broth. As obtained in the sensorial analysis, the storage condition of 10 °C AR was shown to be more efficient in conserving the light bean staining 'BRS Estilo'. In viscosity analysis in Brookfield viscometer, all the storage conditions had higher results compared to storage in natural environmental conditions for both worked cultivars.